The school promoter in Catalonia: a pilot experience between family and school - Núria Llevot-Calvet; Olga Bernad-Cavero (Educazione Interculturale)
Since the 1990s, faced with the arrival in their classrooms of children from foreign countries and ethnic minorities, schools, especially public schools, have had to face new challenges related to cultural and religious diversity. In response to these new emerging issues, and to promote social justice, educational success, equity and equal opportunities, schools have implemented actions and projects in collaboration with other socio-educational agents in the environs. On the other hand, many authors point out the benefits of establishing good relationships and communication between the school and families, for the benefit of the school and teaching staff, the students and the families themselves. However, they also point out the existence of linguistic, cultural, socio-economic and institutional barriers that hinder this. Focusing on Roma pupils and their families, one of the actions implemented in Catalonia in attempts to overcome these barriers and promote the educational success of the pupils, as well as favouring a good relationship with the families, is the figure of the Roma school promoter (intercultural mediator). This article focuses on the analysis of this figure, their functions and the actions they carry out. To this end, it analyses the results of four ethnographies carried out in centres of maximum complexity in Catalonia and the results of documentary analysis and in-depth interviews with professionals and experts on the subject.